Analysis of bacterial genetic diversity in biofloc by using ARDRA 16S-rRNA gene - Widanarni; Nurhayati, Dewi; Wahjuningrum, Dinamella (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT This study aimed to analyze the genetic diversity of bacteria associated in bioflocs using 16S-rRNA polymerase chain reaction (PCR) with ARDRA technique. A total of 38 dominant bacterial isolates was obtained from bioflocs samples and of these isolates, 16S-rRNA gene was then isolated and amplified using PCR. The 16S-rRNA gene of the isolates was then cut using HaeIII (5’-GG↓CC) and HhaI (5’-GCG↓C) restriction enzymes resulting an ARDRA pattern which was further used as the binary data for the construction of phylogenetics tree that was used to estimate the group of bacteria. The result with HaeIII cut restriction enzyme from biofloc-associated bacteria gave 11 ARDRA patterns, while with the restriction enzyme HhaI gave eight ARDRA patterns. Phylogenetics of bacterial populations from biofloc-based cultivation system water consisted of at least 13 different bacterial species. Result of sequencing from two gene sample 16S-rRNA were identified as Microbacterium foliorumand and Pseudomonas putida. Keywords: bacterial diversity, ARDRA, biofloc, phylogeny  ABSTRAK Penelitian ini bertujuan untuk menganalisis keragaman genetika bakteri bioflok menggunakan metode polymerase chain reaction (PCR) 16S-rRNA dengan teknik ARDRA. Sebanyak 38 isolat bakteri dominan yang diperoleh diamplifikasi gen 16S-rRNAnya dengan PCR, kemudian dipotong dengan enzim restriksi HaeIII (5’-GG↓CC) dan HhaI (5’-GCG↓C). Pola ARDRA ini dijadikan data biner sebagai input untuk konstruksi pohon filogenetika yang dapat digunakan untuk memerkirakan jenis bakteri yang ada. Gen 16S-rRNA hasil PCR setelah dipotong dengan enzim restriksi HaeIII didapatkan 11 pola ARDRA, sedangkan dengan enzim restriksi HhaI menghasilkan delapan pola ARDRA. Berdasarkan pohon filogenetika, diketahui populasi bakteri pada air sistem budidaya bioflok sedikitnya terdiri atas 13 jenis bakteri. Berdasarkan sekuensing dari dua sampel gen 16S-rRNA teridentifikasi jenis bakteri Microbacterium foliorum dan Pseudomonas putida. Kata kunci: keragaman bakteri, ARDRA, bioflok, filogenetika